PENGARUH CAMEL TERHADAP KINERJA KEUANGAN BPRS ASAD ALIF KENDAL - Kharisma Nur Aini; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2016)
Bank’s condition is one of the factors that considered before investors invest their money. The profits decline of BPRS Asad Alif in the period 2015 cause decrease in performance. This research is aimed to identify the influence of CAMEL on BPRS Asad Alif Kendal’s financial performance. CAMEL ratio that used in this research is Capital Adequacy Ratio (CAR), Bad Debt Ratio (BDR), Biaya Operasional tehadap Pendapatan Operasional (BOPO), Cash Ratio (CR) and Loan to Deposit Ratio (LDR), meanwhile financial performance valued with Return On Assets (ROA) and Return On Equity (ROE). The analysis technique used in this research is CAMEL analysis, classic assumption test, multiple linear regression test, and hypothesis test using t test and F test. The result of t test is that CAR ,BDR, LDR and CR have no influence to ROA and ROE. BOPO have negative and significance influence to ROA and ROE. CAMEL have positive and significance influence to financial performance.